2020
DOI: 10.1093/nar/gkz1214
|View full text |Cite
|
Sign up to set email alerts
|

Artificial escape from XCI by DNA methylation editing of the CDKL5 gene

Abstract: A significant number of X-linked genes escape from X chromosome inactivation and are associated with a distinct epigenetic signature. One epigenetic modification that strongly correlates with X-escape is reduced DNA methylation in promoter regions. Here, we created an artificial escape by editing DNA methylation on the promoter of CDKL5, a gene causative for an infantile epilepsy, from the silenced X-chromosomal allele in human neuronal-like cells. We identify that a fusion of the catalytic domain of TET1 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…A splicing correction strategy has been applied to CDKL5, developing engineered U1snRNA variants that were able to rescue CDKL5 mRNA splicing, protein synthesis, and function [44]. Other researchers induced escape of CDKL5 from X chromosome inactivation by editing DNA methylation on the promoter of CDKL5 using a dCas9-TET1 fusion protein [45]. Recently, the first proof-of-concept study on gene replacement as a potential approach for the treatment of CDD was published, using adeno-associated virus (AAV)-CDKL5 vectors in in vivo and in vitro models of CDD [46].…”
Section: Review Of Emerging Therapiesmentioning
confidence: 99%
“…A splicing correction strategy has been applied to CDKL5, developing engineered U1snRNA variants that were able to rescue CDKL5 mRNA splicing, protein synthesis, and function [44]. Other researchers induced escape of CDKL5 from X chromosome inactivation by editing DNA methylation on the promoter of CDKL5 using a dCas9-TET1 fusion protein [45]. Recently, the first proof-of-concept study on gene replacement as a potential approach for the treatment of CDD was published, using adeno-associated virus (AAV)-CDKL5 vectors in in vivo and in vitro models of CDD [46].…”
Section: Review Of Emerging Therapiesmentioning
confidence: 99%
“…Although this co-targeting was not under XIST downregulation, SadCas9-VPR-mediated activation of FOXP3 was enhanced by SadCas9-TET1, suggesting an XIST -independent reactivation of FOXP3 by TET1. Likewise, co-targeting of dCas9-TET1 and dCas9-VP64 synergistically reactivates the X-linked CDKL5 from XCI (25). Thus, XIST is likely to be dispensable during the reactivation of X-linked genes from XCI by TET1 with transactivators such as VPR or VP64.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that, for females with cancer, it may be possible to reactivate the non-mutated, inactivated allele for therapeutic purposes. Recent research has shown that X-linked genes can be reactivated from XCI by targeted editing of DNA methylation (25), offering a possibility for targeted reactivation of X-linked genes from XCI.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rescue of X-linked mutations in CDKL5 has been recently demonstrated using dCas9 fused to TET1, a demethylation factor. Demethylation of the CDKL5 promoter by dCas9-TET1 targeting was able to reactive the silenced WT X-allele in vitro [47].…”
Section: Crispr For the Treatment Of Haploinsufficiencymentioning
confidence: 97%